DATA EXCHANGE EVALUATION IN GLOBAL NETWORKS BASED ON INTEGRATED QUALITY INDICATOR OF SERVICE NETWORK - Yevseiev, S. P.; Rzayev, H. N.; Ostapov, S. E.; Nikolaenko, V. I. (Radio Electronics, Computer Science, Control, 2017)
Context. Increasing amount of data circulating in computer systems and networks requires new approaches to the protocols and mechanisms to ensure the user experience and security of information. Evaluation of the communication effectiveness in a computer network is performed on the basis of particular criteria and quality of service indicators in the data exchange protocols in a wide area network (WAN), which does not allow to fully appreciate the quality of service efficiency, taking into account the economic costs of providing the required values of service indicators quality. An important task in this sense is the study of the complex index of efficiency of data exchange in the global computer networks, taking into account the economic costs. Objective. Consideration of the criteria of the complex index service quality, efficiency of cryptographic information protection, and effectiveness of communication in global computer networks in various ways on the basis of the exchange control integrated efficiency indicator, taking into account the economic costs of providing the required quality of service parameter value. Method. The complex index of efficiency, taking into account the economic costs to ensure the required quality of service parameter values in a global computer networks. Results. It was offered the methodics of evaluating data effectiveness in global computer networks, based on a simple multifactor analysis. Proposed and justified a comprehensive indicator of the effectiveness of data exchange, which takes into account, as the specifications (baud rate, probability and packet delivery time, etc.), and economic parameters, such as cost of deployment and network maintenance, and so on. Conclusions. The method of evaluating the effectiveness of the data on a global computer networks, based on a simple multivariate analysis is offered. With the proposed method analyzed the data transmission efficiency in networks with different technologies, such as X.25 (v.34), Frame Relay, Fast Ethernet (0.1Gb, 1Gb, 10Gb, 40 Gb) on the same criteriaIt is shown that today the most effective technology on the set of parameters a 10Gb Ethernet. The novelty of this approach lies in the possibility of technical and economic parameters combination of the communication effectiveness, it allows to introduce an integrated performance indicator. The practical use of the proposed complex index will more accurately assess the effectiveness of communication protocols, which are used in global IP-based networks, the economic costs of deployment and maintenance of the network, the cost of providing the required quality of service indicator.